Personality Traits an Essential Feature of Police Officers’ Job Satisfaction - Eze, Adaobi C.; Elkanah, Onochie G. (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
The study investigated personality traits (agreeableness, conscientiousness, openness to experience, extraversion, neuroticism) as essential features of police officers job satisfaction. One hundred and fourteen (114) police officers participated in the study and they were drawn from Enugu state police command using multi stage sampling technique (balloting & criterion). Participant’s ages range from 20 to 60 years with mean age of 31.01 and S.D of 6.19. Two instruments were used for data collection; Big Five Personality Inventory (John, Donahue, & Kentle 1991) and Hackman and Oldham’s (1975) job satisfaction scale. Two hypotheses were formulated and tested as the study adopted a cross sectional survey design and hierarchical multiple regression was used to analyse the data. Findings indicated that personality characteristics (extraversion) negatively predicted job satisfaction while (conscientiousness) positively predicted job satisfaction. The finding has some practical implication and could be used for recruitment, selection and career development purposes in the Nigerian police force.